Building Green Capabilities through Green Supply Chain Practices - Anggraeni Pratama Indrianto; Titik Kusmantini (Universitas Diponegoro, 2022)
Green capability is the capability of factories to produce more efficiently and competitively in the market in an environmentally friendly manner. This study aimed to analyze the ability of the “Lestari” Women Farmers Group (WFG) to develop their green products and to see the supply chain structure for their green products. This research was conducted using a qualitative research design and the research technique used was a case study. The result of this research was that green capability can be built through the green supply chain in the Sustainable Farmer Group. “Lestari” Women Farmers Group has succeeded in making business access to destination markets and was able to implement green capability quite well because the quality of the products produced was a product that was free of pesticides, chemicals and used natural ingredients as plant fertilizers such as fertilizers from fruit fermentation and rice washing water so that the quality of the vegetables is guaranteed.